How Gender Inequality in Rural Area: A Movie Analysis Through Sociolinguistic Perspective: Bagaimana Ketimpangan Gender di Pedesaan: Sebuah Analisis Film Melalui Perspektif Sosiolinguistik - Muhammad Ali Sukran (INGGARA (Jurnal Pendidikan Bahasa Inggris dan Bahasa Arab), 2022)
Gender discrimination is a serious issue throughout society, particularly in the local context. Unfair treatment of women is viewed as a natural existence, and this issue is hidden by well-ingrained cultural norms. This study examines the gender discrimination that occurs in the local Sasak film "OMJ" entitled “Kemaik Angen” because it was relevant to the current circumstances. This study aim to find out how gender discrimination occurs in local context based on "OMJ" in episode of “Kemaik Angen” film and to determine the effect of gender discrimination based on the sociolinguistic perspective. This movie was chosen to highlight the reality of rural women who face gender discrimination and to help fight for the issue. Gender discrimination is a form of unfair treatment based on gender differences and has an impact on the psychology of the object. This study uses the qualitative descriptive methodology by observing the film to analyse the social phenomena and conducting the interview with the director of the film as additional data. According to this study, gender prejudice is still pervasive and commonplace in the local setting. In terms of the economics, education, and culture, this casts women in the role of objects who are unable to be independent. As long as there is a culture of gender discrimination, women will always come in second, equality of rights and freedom of choice cannot be attained.